2008
DOI: 10.1109/titb.2007.911310
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Infarct Lesions From Single MRI Modality Using Inconsistency Between Voxel Intensity and Spatial Location—A 3-D Automatic Approach

Abstract: Abstract-Detection of infarct lesions using traditional segmentation methods is always problematic due to intensity similarity between lesions and normal tissues, so that multispectral MRI modalities were often employed for this purpose. However, the high costs of MRI scan and the severity of patient conditions restrict the collection of multiple images. Therefore, in this paper, a new 3-D automatic lesion detection approach was proposed, which required only a single type of anatomical MRI scan. It was develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 44 publications
(55 reference statements)
0
14
0
Order By: Relevance
“…In reality, however, there are hundreds of pathologies causing imaging abnormalities with diverse characteristics in different imaging modalities. For example, in stroke lesions, a hemorrhage appears as a bright region and ischemic stroke appears as a dark region in Computed Tomography scans [2], while in T 1 -weighted MR images an infarct lesion is shown with intensities similar to cerebrospinal fluid (CSF) or grey matter (GM) [3]. …”
Section: Introductionmentioning
confidence: 99%
“…In reality, however, there are hundreds of pathologies causing imaging abnormalities with diverse characteristics in different imaging modalities. For example, in stroke lesions, a hemorrhage appears as a bright region and ischemic stroke appears as a dark region in Computed Tomography scans [2], while in T 1 -weighted MR images an infarct lesion is shown with intensities similar to cerebrospinal fluid (CSF) or grey matter (GM) [3]. …”
Section: Introductionmentioning
confidence: 99%
“…Automatic algorithms for segmentation for acute infarct in MRI have been reported [1015]. The unsupervised method developed by Li et al was based on a multistage procedure including image preprocessing, calculation of tensor field, measurement of diffusion anisotropy, segmentation of infarct volume based on adaptive multiscale statistical classification, and partial volume voxel reclassification [11].…”
Section: Introductionmentioning
confidence: 99%
“…Gupta et al identified the infarct slices and the hemisphere automatically in DWI based on the difference in the percentile characteristics of intensity normalized images and parameters of infarct slice identification and infarct hemisphere identification [14]. Shen et al detected infarct lesions based on the voxel intensity segmentation and the spatial location of tissue distribution [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, complex automatic or semi-automatic computer-based segmentation procedures require a large amount of technical resources that may not be available in clinical settings. Furthermore, multi-spectral approaches are not always accessible in clinical practice since the acquisition of all these images is cost-intensive and requires long processing time (Shen et al, 2008). Conversely, FLAIR-based approaches may, in sporadic cases, overestimate the WMH load due to FLAIR typical high intensity appearance in cortical areas, such as the septum pellucidum, and low artifacts in the fourth ventricle where a large percentage of false positive is detected (Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%